2015
DOI: 10.1186/s13104-015-1126-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective Crizotinib schedule for an elderly patient with ALK rearranged non-small-cell lung cancer: a case report

Abstract: BackgroundNon-small-cell lung cancers (NSCLCs) harboring translocations in anaplastic lymphoma kinase (ALK) are highly sensitive to small-molecule ALK kinase inhibitors, such as crizotinib.Case presentationWe describe a case of post-operative local recurrence of lung adenocarcinoma in an 81 year-old male. He underwent radiation and received chemotherapy with docetaxel, but neither treatment regimen was effective. Following identification of ALK rearrangements, crizotinib treatment was initiated. After treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Near CR on intermittent schedule. High WCC, fatigue, anaemia Nil Fukuizumi et al (2015) Japan [ 46 ] To describe management of crizotinib with dose reductions in 1 case Case report, sample = 1, indication: ALK positive NSCLC Dose variation: 250 mg bd, 250 mg od, 250 mg every 3 days, and 250 mg bd every 3 days, with dose interruptions. Licensed monotherapy starting dose:250 mg bd Significant tumor response on escalating to 250 mg bd.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Near CR on intermittent schedule. High WCC, fatigue, anaemia Nil Fukuizumi et al (2015) Japan [ 46 ] To describe management of crizotinib with dose reductions in 1 case Case report, sample = 1, indication: ALK positive NSCLC Dose variation: 250 mg bd, 250 mg od, 250 mg every 3 days, and 250 mg bd every 3 days, with dose interruptions. Licensed monotherapy starting dose:250 mg bd Significant tumor response on escalating to 250 mg bd.…”
Section: Resultsmentioning
confidence: 99%
“…Eight case studies reported a variety of alternative dosing strategies (Table 5 ). These small studies described non-standard dosing practices in patients receiving either imatinib for leukaemia or gastrointestinal stromal tumour (GIST) [ 41 , 44 , 48 ], crizotinib or eroltinib for NSCLC [ 42 , 46 , 47 ], vemurafenib for malignant melanoma [ 45 ], and sunitinib for RCC [ 43 ]. Some of the evaluated strategies included combinations of intermittent dosing, and various dose reductions in response to experienced toxicities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crizotinib was then administrated at a dose of 250 mg twice daily only every 3 day for 13 months with maintenance of the anti-tumor effect, but no information was available on renal function. [9] There is no clear physiopathological explanation for crizotinib influence on renal function. We believe mesenchymal epithelial transition growth factor (c-Met) expression in the normal adult nephron could partially explain this toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was elderly and his body surface area was smaller than that of the average Japanese man, suggesting that his dose of crizotinib (on a dose to body weight basis) might have led to higher trough and peak levels. Fukuizumi et al ( 9 ) reported a successfully treated case in which a modification of the drug schedule was more effective than dose reduction for avoiding severe adverse events. Given the difficulties associated with crizotinib in our case, determining the dosage based on the body surface area (BSA)-rather than body weight-might have been better for avoiding gastrointestinal adverse events.…”
Section: Discussionmentioning
confidence: 99%